Captive Tawny Frogmouths Exhibit Similar Body Temperature Patterns as Wild Individuals - Czenze, Zenon J.; Myers, Mark; Collins, Darin; Brigham, R. Mark (Frontiers in Ecology and Evolution, 2022)
Free-ranging tawny frogmouths (Podargus strigoides) typically defend body temperature (Tb) between 38-40°C during activity and allow it to fall to 29°C during cold evenings. However, this pattern of nightly Tb decline has not been elicited in captivity during short-term respirometry measurements. We used implanted Tb loggers to record the Tb of two captive tawny frogmouths from 24 September – 24 December 2019 to determine if the conditions in captivity would elicit similar Tb patterns to those measured in the wild. We recorded an average Tb of 34.8 ±1.07°C and 35.6 ±0.99°C for the two birds and minimum Tb of 31.0°C and 32.0°C. Minimum daily Tb was correlated between the two individuals, and the minimum Tb of both individuals was correlated with minimum daily Ta. Our results highlight the need to keep birds under appropriate captive conditions to perform physiological research that produces results which mirror responses by individuals in the wild.